(untitled) (Medico Legal Update, 2020)
Background/Objectives: Ultraviolet rays induce erythema, allergy, and skin aging. We investigated the anti-photoaging effect of stem-cell culture media and Polygoni Multifori Radix extract (GMF). Methods/Statistical analysis: An emulsion containing natural GMF and a mixed emulsion containing stem-cell culture medium and Polygoni Multifori Radix emulsion (DMF) were prepared. Photoaging was induced in hairless mice (SKH-1) by irradiation of UVB rays thrice per week for 6 weeks. Pathological changes were examined following 5 or 10 days of emulsion application. Findings: These mice exhibited typical signs of photoaging including increased epithelial thickness, accumulation of abnormal elastic and collagen fibers, and dermal accumulation of inflammatory and mast cells. Photoaging was significantly inhibited in all experimental groups. The group treated with DMF for 10 days showed similar levels of improvement as those observed in the control group. Improvements/Applications: Thus, both natural GMF and DMF can reduce wrinkles caused by photoaging. In addition, our findings verify the potential of GMF and stem-cell culture media as ingredients for anti-photoaging cosmetic products